Editorial EAJPC 9.1. Issue 1 (7th March 2023) - Heylen, Ann; Taylor-Jones, Kate; Vickers, Edward
This editorial is an overview of this edition of the Journal of East Asian Popular Culture . It features a theme that has assumed prominence in East Asia's cultural conversations during the latter half of 2022, namely the role of religion in public life. Five articles examine the engagement of religion with various examples of popular global culture. Two articles deal with popular portrayals of the recent colonial past in postwar Japan and Taiwan. The Book Reviews section features commentary on recently published works that relate to themes discussed in the research articles.